1986
DOI: 10.3382/ps.0651687
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Specific Gravity Method for Estimating the Total Carcass Fat of New York-Dressed Broiler Chickens

Abstract: Four trials were conducted to determine the applicability of a specific gravity method to estimate total New York-dressed carcass fat. Specific gravity values were compared to abdominal fat pad measurements, and total carcass moisture and fat values. Carcasses were produced over a very wide range of total carcass fat, from 6.5 up to 18.8%, by feeding one of five test diets with calorie-to-protein ratios ranging from 61 to 260. Total carcass fat was estimated on each New York-dressed carcass using specific grav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Damron et al (1990) used different Tagetes products (meal, extracts, oleoresins) with free or saponified xanthophylls in broiler diets and observed a better pigmenting efficiency for free lutein than for saponified lutein or lutein/zeaxanthin mixtures. In contrast, Fletcher et al (1986) observed significantly better skin and shank pigmentation in broilers with a saponified marigold product. Calafat et al (2005) used canthaxanthin and paprika oleoresins in combination with Tagetes for broiler skin pigmentation and observed a higher colouring efficiency for the combination of canthaxanthin with Tagetes.…”
Section: Pigmenting Efficacymentioning
confidence: 72%
“…Damron et al (1990) used different Tagetes products (meal, extracts, oleoresins) with free or saponified xanthophylls in broiler diets and observed a better pigmenting efficiency for free lutein than for saponified lutein or lutein/zeaxanthin mixtures. In contrast, Fletcher et al (1986) observed significantly better skin and shank pigmentation in broilers with a saponified marigold product. Calafat et al (2005) used canthaxanthin and paprika oleoresins in combination with Tagetes for broiler skin pigmentation and observed a higher colouring efficiency for the combination of canthaxanthin with Tagetes.…”
Section: Pigmenting Efficacymentioning
confidence: 72%